2019
DOI: 10.1038/s41598-019-54163-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of ISSR-derived SCAR Marker and SYBR Green I Real-time PCR Method for Detection of Teliospores of Tilletia laevis Kühn

Abstract: Common bunt, caused by Tilletia laevis Kühn [syn. T. foetida (Wallr) Liro] and Tilletia tritici (Bjerk.) Wint. [syn. T. caries (DC) Tul.], is an important wheat disease worldwide. To quickly differentiate the closely related fungi T. laevis, T. tritici and Tilletia controversa (a pathogen that causes dwarf bunt of wheat and has been requested as a quarantined pathogen in many countries), a rapid diagnostic and detection method for an ISSR molecular marker was developed for the first time in this study. Based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Currently, molecular techniques to differentiate T. controversa from other similar Tilletia species are mainly focused on genetic diversity (Pimentel et al, 1998;Pimentel, 2000), PCR (Kochanová et al, 2004), repetitive extragenic palindromic PCR (Rep-PCR) (McDonald et al, 2000;Zupunski et al, 2011), primer-mediated asymmetric-PCR (RM-PCR) together with SYBR Green I and Taqman real-time PCR was also constructed with the detection limit of 0.1 fg and 1.0 fg, respectively (Yuan et al, 2009). Pieczul et al (2018) reported to identify Tilletia spp.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, molecular techniques to differentiate T. controversa from other similar Tilletia species are mainly focused on genetic diversity (Pimentel et al, 1998;Pimentel, 2000), PCR (Kochanová et al, 2004), repetitive extragenic palindromic PCR (Rep-PCR) (McDonald et al, 2000;Zupunski et al, 2011), primer-mediated asymmetric-PCR (RM-PCR) together with SYBR Green I and Taqman real-time PCR was also constructed with the detection limit of 0.1 fg and 1.0 fg, respectively (Yuan et al, 2009). Pieczul et al (2018) reported to identify Tilletia spp.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in molecular detection and quantification have showed that standard PCR, SCAR markers and real-time PCR are highly efficient for pathogen detection 16 . Yao et al developed a SCAR marker for T. laevis with a detection limit of 0.4 ng/μl of DNA from T. laevis, and a SYBR Green I real-time PCR method was also successfully developed based on the SCAR marker with a detection limit of 10 fg/μl T. laevis DNA 20 . In this study, the sensitivity of real-time PCR was 100 fg/µl, which was much more sensitive than that of traditional PCR detection methods (5 ng/µl).…”
Section: Discussionmentioning
confidence: 99%
“…The specificity of the SCAR marker was determined with genomic DNA based on three factors 20 , excluding the genomic DNA of T. laevis . First, DNA from the fungal species that shared similarity with T. laevis, including T. controversa and T. caries , was used.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations